Analysis of training in research ethics in the Bachelor of Psychology (UNMDP) - Bogetti, Celeste (2018)
This paper shows the results of two investigations conducted between September 2012-2013 and September 2013-2014, carried out in the context of two scholarships in the category “stimulation of scientific vocations” given by the National Interuniversity Council. The topic of these research were ethical-deontological training in the investigation area in the course of study that compound the bachelor’s degree in psychology of the National University of Mar del Plata. The first research addressed the syllabus of the subjects that compound the investigation area and the perspective of the teachers about those subjects. The second research focused on the same topic but from the perspective of the students who had taken those courses. The methodologies used were the analysis of the TF-IDF factor to analyse the syllabus, and a quantitative and self-administered questionnaire to get the opinion of teachers and students. The results show an acceptable presence of the topic in the syllabus, which is also acknowledged by the professors and the students.